Spillovers from R&D and Other Intangible Investment: Evidence from UK Industries1. (8th September 2016) - Goodridge, Peter; Haskel, Jonathan; Wallis, Gavin
Abstract : Many agree that evidence exists consistent with spillovers from R&D. But is there any evidence of spillovers from a broader range of intangibles, such as software, design or training? We collect investment data for these wider intangibles for a panel of seven UK industries 1992–2007. Using the industry‐level method in the R&D literature, e.g. Griliches (1973 ), we regress industry TFP growth on lagged external knowledge stock growth, where the latter are outside industry measures weighted by matrices based on (a) flows of intermediate consumption or (b) workers. Our main new result is that we find (controlling for time and industry effects) statistically significant correlations between TFP growth and knowledge stock growth in (a) external R&D and (b) total intangibles (excluding R&D). We show our results are robust to controls for imperfect competition and non‐constant returns; likewise they are robust to including foreign R&D, and other controls, and various lags.